Potensi Bakteri Endofit dari Tanaman Jahe Sebagai Agens Pengandali Hayati - Kristianingrum, Sabrina Ayu; Setiawan, Andree Wijaya; Jayanti, Ruth Meike (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The use of synthetic pesticides is not effective in reducing the prevalence of disease because it produces residues and does not support biodiversity. This is an unwise practice and can cause problems in the future. The use of endophytic microorganisms is widely used to control plant diseases and pests, because it is known to have various pathogen inhibition mechanisms. Biological agents that are used to inhibit plant pathogens and have been widely developed, one of which is endophytic bacteria. The purpose of the research was to evaluate the potential of endophytic bacterial isolate from ginger plants as biological control agents. The type of research used is descriptive and exploratory. Sampling of healthy ginger plants was carried out at 5 points in two sub-districts, namely Getasan and Sumowono, Semarang Regency. Isolation is carried out by taking healthy ginger plants from the roots, rhizomes, fronds, and leaves. Characterization and selection of isolates were carried out by testing their phosphate dissolving ability, nitrogen anchoring, amylase and protease activities, and antagonist tests with Fusarium oxysporum in vitro. The results of this study are that (1) 20 pure isolates were successfully isolated consisting of 2 isolates derived from leaves, 4 isolates from fronds, 8 isolates from roots, and 6 isolates from rhizomes; (2) D91 isolate has the potential as a biological agent with an antagonist mechanism of 86.91% supported by protease enzyme activity, able to dissolve phosphate and anchor nitrogen.